Application of PSAK 109 In Organization of Zakat Managers (OPZ) In Sragen District (Baznas, Lazisnu, Lazismu, And Lazku) - Jelita Mustika Sari; Kartika Hendra Titisari; Siti Nurlaela (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study aims to determine and analyze how the application of zakat and infaq / alms accounting in zakat management organizations in Sragen regency. This type of research is qualitative research. The population and sample used are zakat management organizations in Sragen district, by taking a sample using purposive sampling technique and obtained 4 zakat management organizations with comparative descriptive analysis. The results of this study indicate that not all zakat management organizations in Sragen regency have applied zakat and infaq / alms accounting in accordance with SFAS 109. LAZISNU and LAZISMU have applied but for LAZISNU it is not yet complete because reports on changes in assets under management and notes on financial statements are not made. While BAZNAS and LAZKU have not made financial reports, they only present reports on receipt and distribution of funds. Keywords: SFAS 109; Alms; Charity; Financial Statements